(untitled) (Research, Society and Development, 2024)
Infective endocarditis (IE) is an inflammation of the endocardium, often caused by bacteria, viruses, or fungi. Its mortality rate varies depending on the pathogenic agent and complications such as heart failure and embolism. In developed countries, IE is more common in the elderly, due to increased life expectancy and the use of invasive devices, with Staphylococcus sp being a predominant pathogen. In developing countries, however, the disease affects younger individuals, with Streptococcus sp as the main agent. The aim of this article is to present a literature review on the prophylaxis of infective endocarditis caused by Streptococcus viridans according to the 2007 AHA guidelines. These guidelines limit the use of prophylactic antibiotics to high-risk patients, resulting in a significant reduction in prescriptions without an increase in disease incidence. The review highlights the efficacy of prophylaxis in high-risk groups, such as patients with prosthetic valves, and recommends ongoing monitoring of these guidelines to ensure alignment with clinical outcomes.